Factors associated with therapeutic response in acromegaly diagnosed in the elderly in Spain - Biagetti, Betina; Iglesias, Pedro; Villar-Taibo, Rocío; Moure, María-Dolores; Paja, Miguel; Araujo-Castro, Marta; Ares, Jessica; Álvarez-Escola, Cristina; Vicente, Almudena; Álvarez Guivernau, Èlia; Novoa-Testa, Iria; Guerrero Perez, Fernando; et al. (Frontiers in Endocrinology, 2022)
Context Some reports suggest that acromegaly in elderly patients has a more benign clinical behavior and could have a better response to first-generation long-acting somatostatin receptor ligands (SRL). However, there is no specific therapeutic protocol for this special subgroup of patients. Objective This study aimed at identifying predictors of response to SRL in elderly patients. Design Multicentric retrospective nationwide study of patients diagnosed with acromegaly at or over the age of 65 years. Results One-hundred and eighteen patients (34 men, 84 women, mean age at diagnosis 71.7 ± 5.4 years old) were included. Basal insulin-like growth factor type 1 (IGF-1) above the upper limit of normal (ULN) and growth hormone (GH) levels (mean ± SD) were 2.7 ± 1.4 and 11.0 ± 11.9 ng/ml, respectively. The mean maximal tumor diameter was 12.3 ± 6.4 mm, and up to 68.6% were macroadenoma. Seventy-two out of 118 patients (61.0%) underwent surgery as primary treatment. One-third of patients required first-line medical treatment due to a rejection of surgical treatment or non-suitability because of high surgical risk. After first-line surgery, 45/72 (63.9%) were in disease remission, and 16/34 (46.7%) of those treated with SRL had controlled disease. Patients with basal GH at diagnosis ≤6 ng/ml had lower IGF-1 levels and had smaller tumors, and more patients in this group reached control with SRL (72.7% vs. 33.3%; p < 0.04) [OR: 21.3, IC: 95% (2.4–91.1)], while male patients had a worse response [OR: 0.09, IC 95% (0.01–0.75)]. The predictive model curve obtained for SRL response showed an AUC of 0.82 CI (0.71–0.94). Conclusions The most frequent phenotype in newly diagnosed acromegaly in the elderly includes small adenomas and moderately high IGF-1 levels. GH at diagnosis ≤6 ng/ml and female gender, but not age per se, were associated with a greater chance of response to SRL.